2015
DOI: 10.3758/s13414-015-0929-y
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral delay activity tracks the influence of Gestalt grouping principles on active visual working memory representations

Abstract: Recent studies have demonstrated that factors influencing perception, such as Gestalt grouping cues, can influence the storage of information in visual working memory (VWM). In some cases, stationary cues such as stimulus similarity lead to superior VWM performance. However, the neural correlates underlying these benefits to VWM performance remain unclear. One neural index, the contralateral delay activity (CDA) is an event-related potential that shows increased amplitude according to the number of items held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 49 publications
4
44
1
1
Order By: Relevance
“…Upon examination of the grand average plot (see Fig. 4), it appeared that there were differential effects of the experimental conditions on the SPCN at two separate time points: one occurring during an early latency (350-500 ms; SPCN E ) and one during a later latency (500-650 ms; SPCN L ; see similar results in Luria & Vogel, 2011;Peterson, Gözenman, Arciniega, & Berryhill, 2015). To determine whether there were statistically separate effects of Set Size and Mask Condition at the different time points, a Set Size (2) × Mask Condition (2) × Time Point (2) repeated-measures ANOVA was conducted.…”
Section: Erp Analysis and Resultsmentioning
confidence: 68%
“…Upon examination of the grand average plot (see Fig. 4), it appeared that there were differential effects of the experimental conditions on the SPCN at two separate time points: one occurring during an early latency (350-500 ms; SPCN E ) and one during a later latency (500-650 ms; SPCN L ; see similar results in Luria & Vogel, 2011;Peterson, Gözenman, Arciniega, & Berryhill, 2015). To determine whether there were statistically separate effects of Set Size and Mask Condition at the different time points, a Set Size (2) × Mask Condition (2) × Time Point (2) repeated-measures ANOVA was conducted.…”
Section: Erp Analysis and Resultsmentioning
confidence: 68%
“…One example is that the items’ history as moving separately or together affected the grouping ability, such that after an independent movement period, when colored patches shared the same spatial position forming color-color conjunction (which can be seen as a strong proximity cue), these color-color conjunctions were not fully integrated, as indicated by the CDA amplitude that was higher than a condition with the same number of simple colors (Luria and Vogel, 2014). The CDA also revealed that object grouping might take time to establish, so that in the case of stationary colors sharing the same position (and also when the colors were connected by a line), the CDA amplitude gradually decreased during the retention interval (Luria and Vogel, 2011a; Peterson et al, 2015). Remarkably, these studies reveal that although Gestalt cues affect VWM representations, they do not cause grouping in a reflexive and ‘automatic’ manner.…”
Section: Using the Cda To Study Vwmmentioning
confidence: 99%
“…One way of bypassing this constraint is by uniting several features or objects to form a bound representation that can fit within working memory capacity limits. For the current purpose, we refer to the ability to integrate several features such as color and orientation into a bound object representation as the binding ability (Hommel, 2004; Treisman, 1996), and to the process of integrating several objects into one group, as the grouping ability (Peterson et al, 2015; Woodman et al, 2003). The CDA is ideally suited for investigating binding and grouping because any decrease in the number of maintained objects (for example by grouping 2 items into just one VWM representation) should be followed by a similar decrease in the CDA amplitude.…”
Section: Using the Cda To Study Vwmmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, visual displays in which items are grouped by any number of Gestalt organization cues such as proximity, similarity, connectedness or symmetry, yield higher accuracy rates relative to unstructured displays (e.g., Woodman et al, 2003;Rossi-Arnaud et al, 2006;Peterson and Berryhill, 2013;Gao et al, 2015;Jiang et al, 2016;van Lamsweerde et al, 2016). Structured displays appear to benefit performance by reducing cognitive and neural loads due to the compression of maintained information into higher order configurations (i.e., chunks, Miller, 1956), that effectively increases memory capacity (Xu and Chun, 2007;Gao et al, 2011;Luria and Vogel, 2014;Peterson et al, 2015).…”
mentioning
confidence: 99%